The Poetics of the Limit - Woods, Tim. author. aut Link
XVI, 287 p.
Keywords: This book situates Louis Zukofsky's poetics (and the lineage of Objectivist poetics more broadly) within a set of ethical concerns in American poetic modernism. The book makes a strong case for perceiving Zukofsky as a missing key figure within this ethical matrix of modernism. Viewing Zukofsy's poetry through the lens of the theoretical work of Theodor Adorno and Emmanuel Levinas, Woods argues for an ethical genealogy of American poetics leading from Zukofsky through the contemporary school of LANGUAGE poetry. Woods brings together modernism and postmodernism, ethics and aesthetics, in interesting and innovative ways which shed new light on our understanding of this neglected strain of modernist poetics.